Violent, political, and administrative repression of the Chinese minority in Indonesia, 1945-1998 - Heidhues, Mary Somers (UI Scholars Hub, 2017)
Since Indonesian independence, its Chinese minority has been a victim of violent outbreaks, but also of restrictive policies arising from politics and administrative measures. From about 1957, with the closure of Chinese-language schools and subsequent regulations about expression of Chinese culture, many speak of the